Cell Density and Growth Phase as Factors in the Resistance of a Biofilm of Pseudomonas aeruginosa (ATCC 27853) to Iodine - Brown, Matthew L. (1993)
Previous studies have shown that biofilms exhibit enhanced resistance to iodine. Investigations were conducted to determine the relative importance of growth phase versus cell density on biofilm resistance of Pseudomonas aeruginosa (ATCC 27853) to iodine. Cell density is a contributing factor to resistance, whereas growth to the stationary phase is not sufficient to achieve resistance.